Analysis of Implementation Online Learning through Applications the Covid-19 Pandemic at English Department of Cenderawasih State University - Nicodemus Bisse (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Corona Virus is sweeping across the globe, including Indonesia. So that learning process was initially done directly in the classroom becomes online learning or daring. It would also correspond to dictating to the ministry of Indonesia education that hinders the spread of the coronavirus. So learning has been converted into online learning or daring at home. At study English, Study Program also applies the online learning method by taking advantages of online application such as zoom, WhatsApp group, google form and voice note on the subject. WhatsApp application is the most appropriate for applying online learning at English Study Program. An instructor uses this application because it is familiar to both student and instructor and therefore easier to implement. The study was done with a survey through online interview using a google form to all instructors at English Study Program-FKIP. The Data result that the researchers have been obtained indicates that online learning is the only applicate of method for the current Covid-19 pandemic conditions. The lecturer can evaluate students by doing the recourse to see how far the students understanding of receiving online materials. However, some lecturer also judges that online learning is less effective because there are problems with signal power and the student's faculty of personal laptop gadgets. The student has habit for doing online learning up to student absences. The use of online applications is also adjusted to what materials will be presented